Teaching history and combating racism in the classroom: Afro-Brazilian history and cultures in the textbook (TEL Tempo, Espaço e Linguagem, 2021)
The research aims to analyze the possibilities of the teacher in the classroom for the understanding and application of Law no. 10,639 / 2003 and Afro-Brazilian history and culture, in order to articulate with the textbook to express results that are processed with Elementary School classes of the Final Years.